Testing homogeneous spreadsheet grids with the "what you see is what you test" methodology. - Burnett, M.
Although there has been recent research into ways to design environments that enable end users to create their own programs, little attention has been given to helping these end users systematically test their programs. To help address this need in spreadsheet systems (the most widely used type of end-user programming language), we previously introduced a visual approach to systematically testing individual cells in spreadsheet systems. However, the previous approach did not scale well in the presence of largely homogeneous grids, which introduce problems somewhat analogous to the array-testing problems of imperative programs. We present two approaches to spreadsheet testing that explicitly support such grids. We present the algorithms, time complexities, and performance data comparing the two approaches. This is part of our continuing work to bring to end users at least some of the benefits of formalized notions of testing without requiring knowledge of testing beyond a naive level
Keywords: Array-testing problems; Design environments; End users; End-user programming language; Formalized notions; Homogeneous grids; Homogeneous spreadsheet grid testing; Imperative programs; Performance data; Software testing; Spreadsheet systems; Spreadsheet testing; Time complexities; Visual approach; Visual programming